Stakeholder's concepts, perceptions and recommendations on adolescent reproductive healthcare programs and services in Iloilo City - Badayos-Jover, Mary Barby P. (Danyag :the UPV journal of humanities and social sciences, 2004)
"This exploratory study brought forth the commonalities and differences in stakeholder' concepts, perceptions and recommendations concerning adolescent reproductive health (ARH). This is crucial in developing and implementing relevant and effective ARH programs and services fro the general public, especially in a predominantly Roman Catholic country like the Philippines. Focus group discussions and key informant interviews with the identified stakeholder groups were utilized in this study. The study results indicated that there were insufficient knowledge stakeholders. Such lack of knowledge was seen as a significant barrier in developing ARG programs and services in the public health system. There was also a low quality of sex education taught in public elementary and secondary schools, resulting from the inadequate training of teachers in this area. Consequently, stakeholder's recommendations for effective and appropriate ARH programs and services largely point to counseling and IEC public schools. However, certain older stakeholders still do not warmly accept ARH services that touch on sensitive issues like condom distribution in the public health system."